Dealing with shallow groundwater contexts for the modelling of urban hydrology – A simplified approach to represent interactions between surface hydrology, groundwater and underground structures in hydrological models. (October 2021) - Pophillat, William; Sage, Jérémie; Rodriguez, Fabrice; Braud, Isabelle
Abstract: Hydrological modelling can be a relevant tool to support sustainable planning decisions. However, urban hydrological models usually rely on simplified underground representation that may limit their applicability in shallow groundwater environments. This paper introduces a set of modules designed to describe the numerous interactions between subsurface processes and surface hydrology that may occur in such contexts. The modules provide a rather straightforward approach to simulate the influence of the groundwater on the surface as well as the influence of several underground structures (sewer systems, building basements, …) on subsurface storage and the volumes to be managed by the sewerage network. The modules are evaluated by comparison with reference models over a set of theoretical test cases and integrated within the URBS hydrological model. An application to a realistic hypothetical watershed is carried out to illustrate the benefits and the feasibility of these focussed development in existing urban hydrological models. Highlights: An approach is developed to model subsurface components in urban hydrological models. Interactions between groundwater and several underground structures are modelled. The approach enables a total coupling from the surface to the groundwater outlets. It is integrated in an existing model and applied to a hypothetical watershed. The benefits in terms of system understanding and decision support are illustrated.